Chronic HIV-1 Infection Alters the Cellular Distribution of FcγRIIIa and the Functional Consequence of the FcγRIIIa-F158V Variant - Phaahla, Ntando G.; Lassaunière, Ria; Da Costa Dias, Bianca; Waja, Ziyaad; Martinson, Neil A.; Tiemessen, Caroline T. (Frontiers in Immunology, 2019)
Chronic HIV-infection modulates the expression of Fc gamma receptors (FcγRs) on immune cells and their antibody-dependent effector function capability. Given the increasingly recognized importance of antibody-dependent cellular cytotoxicity (ADCC) in HIV-specific immunity, we investigated the cellular distribution of FcγRIIIa on cytotoxic lymphocytes – natural killer cells and CD8+ T cells – and the effect of the FcγRIIIa-F158V variant on ADCC capacity in HIV-infected individuals (n = 23) and healthy controls (n = 23). Study participants were matched for F158V genotypes, carried two copies of the FCGR3A gene and were negative for FcγRIIb expression on NK cells. The distribution of CD56dimFcγRIIIabright and CD56negFcγRIIIabright NK cell subsets, but not FcγRIIIa surface expression, differed significantly between HIV-1 negative and HIV-1 positive donors. NK cell-mediated ADCC responses negatively correlated with the proportion of the immunoregulatory CD56brightFcγRIIIadim/neg cells and were lower in the HIV-1 positive group. Intriguingly, the FcγRIIIa-F158V variant differentially affected the NK-mediated ADCC responses for HIV-1 negative and HIV-1 positive donors. Healthy donors bearing at least one 158V allele had higher ADCC responses compared to those homozygous for the 158F allele (48.1% vs 34.1%), whereas the opposite was observed for the HIV-infected group (26.4% vs 34.6%), although not statistically significantly different. Furthermore, FcγRIIIa+CD8bright and FcγRIIIa+CD8dim T cell subsets were observed in both HIV-1 negative and HIV-1 positive donors, with median proportions that were significantly higher in HIV-1 positive donors compared to healthy controls (18.2% vs 14.1%; P = 0.038, and 15.7% vs 8.3%; P = 0.016, respectively). Using an HIV-1-specific GranToxiLux assay, we demonstrate that CD8+ T cells mediate ADCC through the delivery of granzyme B, which was overall lower compared to that of autologous NK cells. In conclusion, our findings demonstrate that in the presence of an HIV-1 infection, the cellular distribution of FcγRIIIa is altered and that the functional consequence of FcγRIIIa variant is affected. Importantly, it underscores the need to characterize FcγR expression, cellular distribution and functional consequences of FcγR genetic variants within a specific environment or disease state.